2016
DOI: 10.1093/jpepsy/jsv169
|View full text |Cite
|
Sign up to set email alerts
|

Early Maternal Reflective Functioning and Infant Emotional Regulation in a Preterm Infant Sample at 6 Months Corrected Age

Abstract: Maternal RF was associated with infants' self-regulating behavior, providing preliminary evidence for the regulatory role of maternal RF in preterm infants' emotion regulation capacity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 50 publications
1
27
0
1
Order By: Relevance
“…Esbjørn et al (2013) found that low maternal AAI-RF (and not low paternal AAI-RF) was a predictor of higher levels of anxiety in a sample of clinically anxious school-aged children referred for psychological treatment. Heron-Delaney et al (2016) found that preterm infants of high PDI-RF mothers showed the most negative affects as well as more self-soothing behavior during the Still Face procedure, whereas infants whose mothers were rated lower on PDI-RF exhibited the most negative affects during the reunion-episode. It was argued that maternal reflective functioning might promote emotional self-regulation in the child at the time of distress as well as greater trust in maternal responsiveness.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…Esbjørn et al (2013) found that low maternal AAI-RF (and not low paternal AAI-RF) was a predictor of higher levels of anxiety in a sample of clinically anxious school-aged children referred for psychological treatment. Heron-Delaney et al (2016) found that preterm infants of high PDI-RF mothers showed the most negative affects as well as more self-soothing behavior during the Still Face procedure, whereas infants whose mothers were rated lower on PDI-RF exhibited the most negative affects during the reunion-episode. It was argued that maternal reflective functioning might promote emotional self-regulation in the child at the time of distress as well as greater trust in maternal responsiveness.…”
Section: Resultsmentioning
confidence: 89%
“…Three studies (Esbjørn et al, 2013; Heron-Delaney et al, 2016; Smaling et al, 2016b) on child emotion regulation focused on anxiety symptoms in school-aged children, infants’ behavior during the Still Face procedure (Tronick et al, 1978), and infants’ aggressive behavior. Esbjørn et al (2013) found that low maternal AAI-RF (and not low paternal AAI-RF) was a predictor of higher levels of anxiety in a sample of clinically anxious school-aged children referred for psychological treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This ability is referred to as mentalization or reflective functioning (RF) [Fonagy, 1991;Fonagy, Gergely, Jurist, & Target, 2006]. There is mounting evidence that high parental mentalization is associated with higher quality caregiving, attachment security, and successful ER while low parental mentalization is related to impairment in emotional regulation and externalizing behaviors in children [Ensink, Bégin, Normandin, & Fonagy, 2016;Heron-Delaney et al, 2016;Smaling et al, 2016]. Mentalization may play a particularly important role in families of individuals with ASD, as parents have to work harder than others to understand their children's thoughts and intentions, as they have to understand and make sense of what seems to be incomprehensible behavior, often in the absence of a positive response from the child [Slade, 2009].…”
Section: Mentalization and Ermentioning
confidence: 99%
“…Furthermore, early parent–child interactions enhance childrens’ ability to manage their own emotions by communicating them instead of impulsively acting on them. Such management of emotions is useful for children to differentiate their own emotions from those of others and for predicting others’ intentions (Heron‐Delaney et al., ; Rutherford, Goldberg, Luyten, Bridgett, & Mayes, ; Slade et al., 2005). However, when early parent–child interactions are missing or disrupted, and parents are lacking or hostile in mentalizing ability, their children also have a poor ability to differentiate and modulate their emotions, differentiate their emotions from those of others, and develop a coherent sense of agency.…”
Section: Introductionmentioning
confidence: 99%